Examining the Influence of the First Language on Teaching and Learning English as a Second Language (L2): A Linguistic Interference Perspective - Montle, Malesela Edward (International Journal of Language and Literary Studies, 2022)
The first language influences learning English as a second language (L2). This influential role depends mainly on contextual factors such as classroom setting, pedagogical practices and L1 and L2 exposure levels. This denotes that the first language becomes beneficial to the learning of L2 when the contextual factors work in favour of both languages. Several findings in the literature indicate that the first language plays an influential role in English second language learning. The persuasion can be either positive or negative depending on the level of L2 exposure. This study utilized a qualitative descriptive design to examine the influence of the first language on teaching and learning the English language through a linguistic interference perspective. The researchers employed non-participatory observations, and semi-structured interviews as data collection instruments and qualitative content analysis served as a method of data analysis. The findings indicate that the learners’ first language interferes with learning English as a second language and causes hindrances to their academic success. Thus, a subtractive bilingual education is strongly recommended for English to be extensively exposed to learners.